2021
DOI: 10.1016/j.chest.2020.08.2094
|View full text |Cite
|
Sign up to set email alerts
|

A 49-Year-Old Man Presents With Fever of Unknown Origin and Cough

Abstract: A 49-year-old man presented with 3 months of persistent fever, cough, shortness of breath, and chest tightness. He had no response to treatment with antibiotics. He had been treated with an empiric 2-week course of steroids approximately 2 months before presentation, with mild and transient improvement. He did not use tobacco and had not experienced any weight loss, hemoptysis, arthralgia, or myalgia, and was otherwise in good health. He denied contact with anyone with pulmonary TB or other respiratory illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although diagnostic criteria have traditionally focused on rheumatic diseases, since 1972 several RP cases involving valvular heart disease, myasthenia gravis, and myelodysplastic syndrome have been reported, based on histopathological examination after appearance of severe complications[ 12 - 16 ]. Over the last two decades, the medical literature reported also an increasing number of RP cases associated with bronchopulmonary symptoms[ 17 - 20 ]. One prospective study found that among all RP patients, those with predominant respiratory symptoms were younger and had a higher intensive care unit (ICU) admission rate[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although diagnostic criteria have traditionally focused on rheumatic diseases, since 1972 several RP cases involving valvular heart disease, myasthenia gravis, and myelodysplastic syndrome have been reported, based on histopathological examination after appearance of severe complications[ 12 - 16 ]. Over the last two decades, the medical literature reported also an increasing number of RP cases associated with bronchopulmonary symptoms[ 17 - 20 ]. One prospective study found that among all RP patients, those with predominant respiratory symptoms were younger and had a higher intensive care unit (ICU) admission rate[ 21 ].…”
Section: Discussionmentioning
confidence: 99%